Islam Denounces Terrorism - Harun Yahya (GHQ, Rawalpindi Services Book Club, 2014)
This book maintains that the source of the terror that we condemn is definitely not from a divine religion, and that there is no room for terrorism in Islam. This is made clear in the Qur'an, the main source of Islam, and in the practices of all true Muslim rulers, the Prophet Muhammad being the foremost of them.
One of the unfortunate effects of 9/11 was the misperception that terrorism has divine approval in Islam. Islam Denounces Terrorism thoroughly debunks this notion by looking at both the Qur$1 (Ban and the historical record. With extensive color illustrations, the book covers such timely topics as Islamic morality, how the Qur$1 (Ban views war, the real face of the terrorists who act in the name of religions, and much more.s
Include Illustrations and Notes.
The author, who writes under the pen-name HARUN YAHYA, was born in Ankara in 1956. Having completed his primary and secondary education in Ankara, he then studied arts at Istanbul's Mimar Sinan University and philosophy at Istanbul University. Since the 1980s, the author has published many books on political, faith-related and scientific issues. Harun Yahya is well-known as an author who has written very important works disclosing the imposture of evolutionists, the invalidity of their claims and the dark liaisons between Darwinism and bloody ideologies such as fascism and communism.
Keywords: Terrorism--Prevention -- Islam and secularism -- Islam and social problems -- Terrorism--Religious aspects--Islam -- Evolution (Biology)--Religious aspects--Islam -- Islam